The Unbearable Humanum: Reflecting Back, Working Forwards - Kirwan, Michael (New blackfriars, 2015)
This article, “reflects back and works forwards”, by thinking together the three “sorrowful mysteries” of the last one hundred years; three marked and irrevocable steps of escalation and complexity in the history of international conflict. Along with so many others in this centenary year, we commemorate: its causes, and the lessons to be learned. What are the continuities between the Great War, 1914–18, and the second “sorrowful mystery”, the advent of nuclear weapons? This brings us to the specific challenges that face us in the present: globalized violence in the name of religion, the reactive “war on terror” and the development of “smart” technology, remind us that our context too is unprecedented and uniquely dangerous. Explanatory avenues opened up include discussion of the moral and political implications of unmanned weapons, or drones. Here is an example of the crisis of sacrifice associated with René Girard, while Girard's own recasting of Clausewitz's notion of the “escalation to extremes”, and the humanism in Edward Schillebeeckx are also examined.